Case Study: The Acceptance of XYZ Bank’s Mobile Banking Application Using Technology Acceptance Model (TAM) - Gabriella Juliani; Nike Taruna; Martha Anastasia Sibarani; Yenny Yenny (Profesional Muda Cendekia Publishing, 2021)
Nowadays, it is common for public to use information technology to support each daily needs, such as mobile banking application. One of largest bank in Indonesia, XYZ Bank provided mobile banking application to support customer in doing financial and banking transaction. The case study was done to examine the customer’s acceptance of XYZ Bank’s mobile banking application by using Technology Acceptance Model (TAM), in order to provide information regarding factors affecting customer’s preference in using mobile banking application and improve XYZ Bank’s mobile banking application. This study was using quantitative research strategy, in which data was collected by conducting online survey towards XYZ Bank customer. Questionnaire was given in 5 point-scale. Technology Acceptance Model (TAM) was conducted to examine the effect between variables, such as: perceived ease of use, perceived usefulness, attitude towards using, behavioral intention, actual use, and trust. The researcher found that all indicators are reliable, based on its Cronbach’s Alpha value which ranges between 0.725 (actual use) and 0.924 (perceived ease of use). Data validity was tested and shows the Chi-square difference ranges from 69.716 (between trust and perceived usefulness) to 106.715. As conclusion, researcher concluded that all hypotheses are accepted and each variable had positive effect towards other variable.